IN SILICO EVALUATION OF ANTICANCER ACTIVITY, DRUG-LIKENESS, PHARMACOKINETIC PROPERTIES, AND TOXICITY PROFILES OF ALKALOID COMPOUNDS FROM Toddalia asiatica Lamk: VALUASI IN SILICO AKTIVITAS ANTIKANKER, KEMIRIPAN OBAT (DRUG-LIKENESS), SIFAT FARMAKOKINETIK, DAN PROFIL TOKSISITAS SENYAWA ALKALOID DARI Toddalia asiatica Lamk - Dofea Tristan Brilliance; Alwan Aulia; Abid’Bie Ya Samantha; Astaria Tasya; Fransisco Varius Dirly; Kasih Kasih; Febian Selvano Basule; Dodi Iskandar (PT. ROCE WISDOM ACEH, 2026)
Toddalia asiatica Lamk is a medicinal plant known to contain various bioactive secondary metabolites, particularly alkaloids, with potential pharmacological activities. This study aimed to evaluate the anticancer potential, drug-likeness, pharmacokinetic properties, medicinal chemistry characteristics, and toxicity profiles of bioactive compounds from Toddalia asiatica using in silico approaches, including PASS prediction, SwissADME, and pkCSM analysis. PASS prediction results demonstrated that all studied compounds exhibited potential antineoplastic and apoptosis-inducing activities with varying probabilities. Norchelerythrine showed the highest antineoplastic activity, while several other alkaloids, such as dihydrochelerythrine and dihydroavicine, also demonstrated strong anticancer potential. SwissADME analysis revealed that all compounds met Lipinski's Rule of Five, the Ghose Filter, the Veber rule, the Egan rule, and the Muegge rule, indicating favorable drug-likeness and oral bioavailability potential. The compounds also showed moderate water solubility, high gastrointestinal absorption, and good membrane permeability, supporting their potential as oral drug candidates. Pharmacokinetic evaluation indicated relatively good distribution profiles, moderate tissue distribution, and low-to-moderate blood-brain barrier permeability, which may reduce the risk of neurological side effects. Medicinal chemistry analysis showed no PAINS or BRENDA alerts, suggesting that the compounds are free of problematic chemical fragments and exhibit good lead-likeness characteristics. Synthetic accessibility values ranged from moderate to relatively easy, indicating feasibility for chemical synthesis and optimization. Toxicity prediction revealed moderate toxicity profiles with acceptable maximum tolerated doses, relatively low acute toxicity, and manageable chronic toxicity risks. Although several compounds showed potential aquatic toxicity, the overall safety profiles remained acceptable for early-stage drug development. Among all compounds, norchelerythrine and dihydroavicine demonstrated the most promising combination of biological activity and pharmacokinetic properties. Overall, the findings suggest that alkaloid compounds from Toddalia asiatica possess strong potential as natural product-based anticancer drug candidates. However, further in vitro and in vivo studies are required to validate their biological activity, pharmacokinetics, and safety before clinical application.